Lysosomal storage diseases - Platt, F; D'Azzo, A; Davidson, B; Neufeld, E; Tifft, C (Springer Nature, 2018)
Lysosomal storage diseases (LSDs) are a group of over 70 diseases that are characterized by lysosomal dysfunction, most of which are inherited as autosomal recessive traits. These disorders are individually rare but collectively affect 1 in 5,000 live births. LSDs typically present in infancy and childhood, although adult-onset forms also occur. Most LSDs have a progressive neurodegenerative clinical course, although symptoms in other organ systems are frequent. LSD-associated genes encode different lysosomal proteins, including lysosomal enzymes and lysosomal membrane proteins. The lysosome is the key cellular hub for macromolecule catabolism, recycling and signalling, and defects that impair any of these functions cause the accumulation of undigested or partially digested macromolecules in lysosomes (that is, ‘storage’) or impair the transport of molecules, which can result in cellular damage. Consequently, the cellular pathogenesis of these diseases is complex and is currently incompletely understood. Several LSDs can be treated with approved, disease-specific therapies that are mostly based on enzyme replacement. However, small-molecule therapies, including substrate reduction and chaperone therapies, have also been developed and are approved for some LSDs, whereas gene therapy and genome editing are at advanced preclinical stages and, for a few disorders, have already progressed to the clinic.